2013
DOI: 10.1172/jci66204
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin-treated human endothelial cells preferentially activate allogeneic regulatory T cells

Abstract: Human graft endothelial cells (ECs) can act as antigen-presenting cells to initiate allograft rejection by host memory T cells. Rapamycin, an mTOR inhibitor used clinically to suppress T cell responses, also acts on DCs, rendering them tolerogenic. Here, we report the effects of rapamycin on EC alloimmunogenicity. Compared with mock-treated cells, rapamycin-pretreated human ECs (rapa-ECs) stimulated less proliferation and cytokine secretion from allogeneic CD4 + memory cells, an effect mimicked by shRNA knockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 85 publications
2
92
0
Order By: Relevance
“…A rapid partition of ISDs into cells would appear to explain our observations of increased suppression by brief pretreatments of MSCs, fibroblasts, APCs and HUVECs and may explain at least part of the increased suppression reported for rapamycintreated endothelia and Tregs [30,36].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A rapid partition of ISDs into cells would appear to explain our observations of increased suppression by brief pretreatments of MSCs, fibroblasts, APCs and HUVECs and may explain at least part of the increased suppression reported for rapamycintreated endothelia and Tregs [30,36].…”
Section: Discussionmentioning
confidence: 76%
“…The same number of untreated cells had no apparent effect, and, even a dose of 2 Â 10 6 , similar to that used in other studies [37,38], showed only a trend toward greater survival. Whereas rapamycin alone has been used for prevention of solid-organ transplant rejection and aGVHD in mice transplant models [30,31], doses of 3 Â 50 mg were insufficient in our experiments, as was a single dose of 50 ng that we calculate to be the approximate amount of drug introduced by the pretreated MSC (data not shown). Therefore, whereas the suppressive effects of MSCs and rapamycin were seen to be additive in vitro, synergism is indicated by the in vivo model.…”
Section: Discussionmentioning
confidence: 82%
“…IL-2, as well as other growth-promoting cytokines, activates mTOR. In this scenario, rapamycin functions to inhibit lymphocyte proliferation, costimulator molecule expression, and cytokine production (82). mTOR inhibition also promotes the generation of CD4 ϩ FoxP3 ϩ regulatory T (Treg) cells both in vitro and in vivo (45).…”
Section: Role Of Mtor In Immune Regulationmentioning
confidence: 99%
“…Furthermore, alloAbs, that portend poor long-term graft outcome in kidney transplantation, are thought to contribute to this pathogenic process by mediating HLA-I molecule ligation on EC surfaces. Wang et al (82) have shown recently that RAPA-pretreated human vascular EC can dampen Tmem proliferation and cytokine production (IL-2 and IFNg), while upregulating their co-inhibitory molecule expression (PDL-1 and PDL-2) in vitro. Furthermore, they enrich for Treg among CD25 þ activated T cells.…”
Section: Vascular Endothelial and Smooth Muscle Cellsmentioning
confidence: 99%